Molecular characterization and prevalence study of stomach ulcer using standard techniques at Nnewi north local government area, Anambra state - Onwuasoanya, Uche F.; Umedum, Chinelo U.; Inwelegbu, Ogochukwu M. T. B.; Nwachukwu, Ebele P.; Egbe, Patricia A.; Akulue, Justina C. (International Journal of Research in Medical Sciences, 2025)
Background: Abnormality in one part of the body is capable of generating pandemonium in all body parts, which interferes with the normal body physiology and standard of living. This study was undertaken to evaluate the prevalence of stomach ulcer using standard techniques at Nnewi North Local Government Area, Anambra State. Methods: Four hundred (400) samples were aseptically collected from participants using a well-capped sterile container and analyzed for the presence of Helicobacter pylori (H. pylori) using immunochromatographic assay for Stool Antigen Test (SAT) and Blood Antibody Test (BAT), Enzyme-linked Immunosorbent Assay ELISA for gamma Immunoglobulin (IgG) and mu immunoglobulin (IgM)], conventional culture technique on selective Columbia blood agar base plus antibiotic and Vitalex growth supplement (Oxoid, England) was used for isolation of H. pylori. The bacterial isolate was characterized based on cultural, morphological, biochemical, and molecular characteristics [Polymerase Chain Reaction (PCR)]. Results: The highest number of H. pylori was detected using ELISA technique at Otolo community 48 (24.0 %)] followed by culture technique (CT) at Umudim community [32(16.0 %), while the least was SAT at Otolo community 2 (1.0 %). Molecular characterization revealed certain strains of H. pylori such as H. pylori strain K154 (HPK154) complete genome, Helicobacter pylori strain BS07 (HPBS07) complete genome, Helicobacter pylori strain K93 (HPK93) complete genome, and Helicobacter pylori strain K115 (HPK115) complete genome. Conclusions: Therefore, the prevalence of stomach ulcer in the sampled communities is high, especially at Otolo community, while ELISA proved to be the best diagnosing technique for accurate detection of Helicobacter pylori.